DEVELOPMENT OF HAZARD IDENTIFICATION GAME MODULE THROUGH GDD TO GROW PRO-SAFETY BEHAVIOR IN GRAPHIC ENGINEERING VOCATIONAL STUDENTS - Elviana Elviana (Jurnal Ilmiah Publipreneur, 2022)
The goal of this research is to create a desktop game-based gaming module for students majoring in graphic engineering. A research and development design was used in this work (R N D). For this study's analysis of the demands of students in occupational safety and health, 54 graphic engineering students were used. Following that, two media and health promotion specialists were used to determine whether the game's development was genuine. This study led to the creation of a game module in the form of a GDD (Game Design Document). The module's quality has been rated as good and requires to revise.